2020
DOI: 10.1002/celc.202000391
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Evolution Reaction on Tin Oxides Supported Iridium Catalysts: Do We Need Dopants?

Abstract: Application of oxide supports is considered as a viable approach to decrease iridium loading in oxygen evolution reaction catalysis in acid electrolyte. While the most of the promising oxides are poor conductors, the need for doping is typically taken as granted, and a representative example is tin dioxide. There are still, however, serious concerns on the feasibility of this approach as we lack consensus on any activity gain by using such oxides, while doubts on stability are numerous. In this work, a set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 53 publications
(44 reference statements)
3
74
0
Order By: Relevance
“…The instability of ATO supports in high potential conditions has been ascribed to the preferential leaching of Sb atoms segregated at their surface. 16,32,[44][45][46][47] .…”
Section: Determination Of S-number Values For Supported and Unsupported Irox Catalystsmentioning
confidence: 99%
“…The instability of ATO supports in high potential conditions has been ascribed to the preferential leaching of Sb atoms segregated at their surface. 16,32,[44][45][46][47] .…”
Section: Determination Of S-number Values For Supported and Unsupported Irox Catalystsmentioning
confidence: 99%
“…Another difference in Ir catalysts' stability is related to the oxidation state of the nanoparticles. The hydrous (amorphous) IrO x is less stable than rutile (crystalline) IrO 2 , [57,69,91,92] and it was previously shown that on the same support (ATO), IrO x was dissolving more during cleaning cycles than its IrO 2 counterpart. [57] In our case, Ir XRD diffraction peaks of the "asprepared" samples are similar (Figure 1), which suggests that all samples contain Ir with the same oxidation state.…”
Section: Stability Evaluationmentioning
confidence: 99%
“…Additionally, the stability and electronic catalyst–support interactions, as well as the economic criteria, need to be taken into account. 11 , 14 16 Given the stated requirements, a promising substitute for carbon is titanium oxynitride (TiON x ), which can be prepared from titanium dioxide (TiO 2 ) 17 or titanium nitride (TiN) 18 in the form of various nanostructures. 19 21 There are different synthesis methods to choose from.…”
Section: Introductionmentioning
confidence: 99%